The Challenges of Sharia Pawnshops in Indonesia in The Era of The Industrial Revolution 4.0 - Nicho Hadi Wijaya (El-Mashlahah, 2022)
The development of the Islamic financial system in Indonesia is marked by the establishment of various Islamic financial institutions and the issuance of various sharia-based financial instruments. Essentially, Islamic financial institutions are different from conventional financial institutions, in terms of mechanisms, objectives, powers, scope, and responsibilities. The provisions and discourses contained in classical fiqh on Rahn are then adapted to modern economic developments and synergized with the needs of today's society. With the majority of the Muslim population, it is not difficult for Sharia Pawnshops in Indonesia to develop their business. Sharia pawnshops are expected to be able to conduct campaigns to the public about the use of sharia-based products. However, there are still various problems in developing sharia pawnshops in Indonesia. And, an analysis needs to conduct to uncover obstacles and find solutions in an effort to develop sharia pawnshops. The type of the research was normative legal research using a qualitative descriptive approach. The study indicates that Sharia Pawnshops are one of the financial institutions that provide effective alternative funding for the community. The growth of pawnshop profits which continues to grow in the era of the industrial revolution 4.0 and during the Covid-19 pandemic is one indicator of the success of sharia pawnshop management. In addition, sharia pawnshops can prove that they can prioritize Islamic moral values during the rapid development of financial institutions in Indonesia. However, from all of this, there are problems that need to be evaluated to improve the performance of sharia pawnshops in the future.